Implemetnasi Metode Fuzzy Associative Memory Dalam Menentukan Tingkat Kepuasan Pelayanan Di Perpustakaan - Yakub, Suardi; Azanuddin, A; Prayudha, Jaka (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2022)
Creating satisfaction with the library is certainly not easy, librarians must be able to provide quality services, both directly and indirectly to students, good service can certainly be of more value than librarians to students. less friendly in serving users who need information. For this reason, a Decision Support System that applies Fuzzy Associate Memory was developed to determine the level of satisfaction of library services at STMIK Triguna Dharma. In general, Decision Support Systems are computer-based information systems, including knowledge-based systems that can be used in making decisions in organizations or companies. The level of user satisfaction makes it easy for STMIK Triguna Dharma in evaluating the extent to which the quality they provide in the library is related to data on library facilities, services, and convenience. is quite satisfying.